Metacommunity process rather than continental tectonic history better explains geographically structured phylogenies in legumes. - Lavin, M; Schrire, B; Lewis, G; Pennington, RT; Delgado-Salinas, A; Thulin, M; Hughes, C; Matos, AB; Wojciechowski, M (2004)
Penalized likelihood estimated ages of both densely sampled intracontinental and sparsely sampled transcontinental crown clades in the legume family show a mostly Quaternary to Neogene age distribution. The mode ages of the intracontinental crown clades range from 4-6 Myr ago, whereas those of the transcontinental crown clades range from 8-16 Myr ago. Both of these young age estimates are detected despite methodological approaches that bias results toward older ages. Hypotheses that resort to vicariance or continental history to explain continental disjunct distributions are dismissed because they require mostly Palaeogene and older tectonic events. An alternative explanation centring on dispersal that may well explain the geographical as well as the ecological phylogenetic structure of legume phylogenies is Hubbell's unified neutral theory of biodiversity and biogeography. This is the only dispersalist theory that encompasses evolutionary time and makes predictions about phylogenetic structure.